Communicating Resistance: A Narrative Analysis of Women’s Struggle Against Tyranny - Alensky Perlika; Sukmawati, Lilis (Al-MUNZIR, 2025)
Women's resistance against the authoritarianism of the New Order is the socio-political context of Indonesia during the leadership of President Soeharto. In the book "Berjuang Melawan Tiran" written by 42 authors, it provides motivation from the side of resistance to fight oppression. This study aims to find out how the analysis of women's resistance against the authoritarianism of the New Order is described in the book entitled "Berjuang Melawan Tiran" using Tzetan Todorov's narrative theory, namely, conditions of balance, disturbance, awareness of disturbance, to repair the disturbance, new balance. The research method uses literature studies. The results of the study obtained equilibrium (initial balance) starting from the normal life of women before the conflict as students or workers, disruption (disruption) from the New Order regime created injustice and violence, recognition (awareness of disturbance) awareness that the struggle also concerns gender inequality and patriarchy, repair (efforts to repair disturbances) building organizations and continuing after the reform, new equilibrium (new balance) formed a new awareness even though the struggle is now more individual and full of challenges. This research demonstrates the author's real-life experiences, demonstrating how feminist theory and narrative analysis of the New Order can be used together to gain a better understanding of the complexities of resistance that motivated other women to defend social equality.